Media Image of Artificial Intelligence in Telegram News Channels: Sentiment Analysis and Discourse Interpretation - Oksana V. Goncharova; Anna V. Lipatova; Galina V. Napreenko (Виртуальная коммуникация и социальные сети)
The authors analyzed the discourse strategies and topics involved in the media image of artificial intelligence in Telegram news channels (RIA Novosti, Mash, Live broadcast • News, Topor Live). A quantitative and qualitative sentiment analysis of Telegram posts made it possible to interpret the results from a discursive perspective, taking into account the socio-political and cultural context, as well as to analyze the impact of these representations on public perception and discussions about technological progress. The data were samples using a GitHub parser and manually verified. The discourse interpretation and sentiment analysis involved ranking sentences into thematic blocks that constructed the image of artificial intelligence. The linguistic analysis of news contexts demonstrated mostly positive and neutral modality. The key linguistic means included verbs of creative, intellectual, and service actions. Verbs of destruction and emotional-evaluative vocabulary were responsible for the negative sentiment. The texts revealed a strong metaphorization of artificial intelligence as help. Artificial intelligence was represented as a technology that can benefit humans, but is potentially dangerous and requires strict control. The assessment method remains debatable for multitopic texts, as well as the relationship between sentiment analysis and manual analysis of the discursive representation of a media image.